2019
DOI: 10.1016/j.cognition.2019.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Mental attribution is not sufficient or necessary to trigger attentional orienting to gaze

Abstract: Attention can be shifted in the direction that another person is looking, but the role played by an observer's mental attribution to the looker is controversial. And whether mental attribution to the looker is sufficient to trigger an attention shift is unknown. The current study introduces a novel paradigm to investigate this latter issue. An actor is presented on video turning his head to the left or right before a target appears, randomly, at the gazed-at or non-gazed at location. Time to detect the target … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 20 publications
3
13
0
Order By: Relevance
“…This replicates findings from previous studies showing that even very basic social-cognitive processes like gaze cueing can be top-down modulated by social context information [53], and highlights that certain top-down modulators, such as the physical appearance of an agent, might only exert their effect in relatively lifelike interactions. This observation also provides some clarity regarding the ongoing debate in the literature whether manipulations related to mind perception and/or mentalizing have an effect on social attention [54] or not [55]. The current study suggests that there is an interaction between top-down and bottom-up mechanisms influencing social attention, but that the topdown component might only take effect in sufficiently realistic paradigms (see also [56]).…”
Section: Discussionsupporting
confidence: 57%
“…This replicates findings from previous studies showing that even very basic social-cognitive processes like gaze cueing can be top-down modulated by social context information [53], and highlights that certain top-down modulators, such as the physical appearance of an agent, might only exert their effect in relatively lifelike interactions. This observation also provides some clarity regarding the ongoing debate in the literature whether manipulations related to mind perception and/or mentalizing have an effect on social attention [54] or not [55]. The current study suggests that there is an interaction between top-down and bottom-up mechanisms influencing social attention, but that the topdown component might only take effect in sufficiently realistic paradigms (see also [56]).…”
Section: Discussionsupporting
confidence: 57%
“…Studies have consistently shown that people are faster at responding to valid trials compared to invalid trials, with the magnitude of the difference between valid reaction times and invalid reaction times indicative of how strongly or how frequently attention was oriented to the gazed-at location (i.e., the gaze-cueing effect: GCE). Studies investigating the GCE have also shown that the effects are observed even when gaze was counterindicative of the target location, which suggests the reflexivity of attention orienting to gaze cues (Ristic and Kingstone, 2005;Kingstone et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have speculated that this effect is better explained by shifts in attention to salient cues, which only happen to be social (Cole et al, 2019). Similarly, research shows that gaze cueing effects can persist in spite of the gazing agent being obstructed from viewing the target stimulus by a physical barrier (Cole et al, 2015), and attributing mental states onto the gazing face, or the acting agent behind the face is neither sufficient nor necessary for automatic shifts of social attention to occur in gaze cueing paradigms (Kingstone et al, 2019). Given these limitations of the gaze cueing paradigm and the interpersonal joint reaching paradigm, our own research has investigated social attention using an interactive version of the original spatial cueing paradigm (Posner & Cohen, 1984).…”
Section: Social Attentionmentioning
confidence: 99%